2020
DOI: 10.22541/au.160571540.02057981/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 and Multisystem Inflammatory Syndrome in Children: A Systematic Review and Meta-analysis

Abstract: Background: Multisystem inflammatory syndrome in children (MIS-C) associated with COVID-19 has been increasingly recognized. However, the clinical features of MIS-C and the differences from Kawasaki disease remain unknown. The study aims to investigate the epidemiology and clinical course of MIS-C. Methods: PubMed and EMBASE were searched through August 30, 2020. Observational studies describing MIS-C were included. Data regarding demographic features, clinical symptoms, laboratory, echocardiography and radiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
2
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(67 citation statements)
references
References 0 publications
5
52
2
8
Order By: Relevance
“…Hence, human ACE2 expressing mice facilitate investigations of the pathogenesis of severe COVID-19 by, e.g., histopathological analyses at varying time points after infection, measuring the cytokine responses ( Israelow et al, 2020 ; Oladunni et al, 2020 ) or analyzing the transcriptome of lungs of diseased mice ( Han et al, 2020 ). However, this mouse model currently does not reflect all aspects of COVID-19, since unusual features such as the hyperinflammatory syndromes that are sometimes seen in children ( Yasuhara et al, 2021 ) have not been observed in human ACE2 mice. Nevertheless, as human ACE2 expressing mice shed high viral titers and efficiently transmit SARS-CoV-2 to naïve in-contact animals ( Bao et al, 2020b ), they represent a useful model for transmission studies.…”
Section: Animal Models In Sars-cov-2 Researchmentioning
confidence: 99%
“…Hence, human ACE2 expressing mice facilitate investigations of the pathogenesis of severe COVID-19 by, e.g., histopathological analyses at varying time points after infection, measuring the cytokine responses ( Israelow et al, 2020 ; Oladunni et al, 2020 ) or analyzing the transcriptome of lungs of diseased mice ( Han et al, 2020 ). However, this mouse model currently does not reflect all aspects of COVID-19, since unusual features such as the hyperinflammatory syndromes that are sometimes seen in children ( Yasuhara et al, 2021 ) have not been observed in human ACE2 mice. Nevertheless, as human ACE2 expressing mice shed high viral titers and efficiently transmit SARS-CoV-2 to naïve in-contact animals ( Bao et al, 2020b ), they represent a useful model for transmission studies.…”
Section: Animal Models In Sars-cov-2 Researchmentioning
confidence: 99%
“…[15][16][17] A mediana de idade dos casos de SIM-P no Brasil foi inferior à encontrada na maioria dos estudos, [2][3][4][5][12][13][14][15][16][17] aproximando-se da síndrome de Kawasaki (SK) ou da COVID-19 aguda pediátrica. [18][19][20] Esse resultado pode indicar que os serviços de saúde no Brasil foram mais sensíveis à suspeição da SIM-P em crianças/adolescentes mais jovens, ou que o estudo incluiu casos de outras manifestações inflamatórias semelhantes à SIM-P. A sobreposição com outras síndromes multissistêmicas já foi descrita em diversos trabalhos. 2,18,20 A elevada frequência de crianças com menos de 1 ano também chamou a atenção, especialmente entre os que evoluíram para óbito, justamente um grupo etário que apresenta desafio ainda maior para diagnóstico.…”
Section: Discussionunclassified
“…[18][19][20] Esse resultado pode indicar que os serviços de saúde no Brasil foram mais sensíveis à suspeição da SIM-P em crianças/adolescentes mais jovens, ou que o estudo incluiu casos de outras manifestações inflamatórias semelhantes à SIM-P. A sobreposição com outras síndromes multissistêmicas já foi descrita em diversos trabalhos. 2,18,20 A elevada frequência de crianças com menos de 1 ano também chamou a atenção, especialmente entre os que evoluíram para óbito, justamente um grupo etário que apresenta desafio ainda maior para diagnóstico. 16 A maior frequência de casos de SIM-P em pessoas da raça/cor da pele parda e do sexo masculino foram consistentes com a literatura; 2,4,14-16 porém, a contribuição dos fatores genéticos permanece pouco elucidada e acredita-se que os resultados podem estar relacionados a fatores ambientais, como iniquidades sociais e raciais.…”
Section: Discussionunclassified
See 2 more Smart Citations